Response Of Cattleya Orchid Subculture Growth with Various Types and Concentrations of Sweet Potato (Ipomoea batatas L.) Extracts - Aisya Nabila Maharani; Susiyanti; Andi Apriany Fatmawaty; Sulastri Isminingsih (Jurnal Agroekoteknologi Terapan, 2025)
Cattleya orchid is a large-flowered ornamental plant known for its vibrant color and pleasant fragrance. The challenges of conventional propagation and high market demand have prompted the use of in vitro techniques. The success of in vitro propagation is highly influenced by the culture medium, which can be enriched with organic sources such as sweet potato extract, a rich source of vitamins and carbohydrates. This study aims to evaluate the effect of different types and concentrations of sweet potato extract on the growth of Cattleya orchid subcultures. This experiment used a Randomized Block Design (RBD) with two factors: sweet potato types (white, yellow, purple) and extract concentrations (50, 100, 150, and 200 g L-1), analyzed using ANOVA and Duncan’s Multiple Range Test at 5% significance level. The results showed that the purple sweet potato yielded the highest explant height increase (0,90 cm), while the interaction of white sweet potato with 50 g L-1 extract concentration produced the highest leaf number (1.77 leaves). The addition of sweet potato extract supports the in vitro growth of Cattleya orchid subcultures. Keywords: Cattleya, orchid, in vitro, sweet potato extracts, growth, subculture